PERAN DA’I DALAM MENJAGA KELESTARIAN ALAM - Akhmad Syahid (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2018)
Allah Subhanahu wa Ta’ala, created the complete universe and its contents, and created in a balanced, paired and interconnected relationship between one being and another. Of the creatures created by Allah Subhanahu wa Ta’ala, on this earth, the most utilizing the contents of this earth is human, because humans can benefit and plants and animals. Humans are given the power to eat from the kinds of animals and plants. But in reality, the universe continues to be damaged, both in the ocean and on the land. Then it affects the declining quality and quantity of the creatures that live on it. Da’i is a person who has the duty to preach and spread the teachings of Islam to all mankind. Da’wah submitted or spread in da’i should touch every line of human cases, including in it is the duty of every human being to maintain, care for and create a beautiful universe. The advantages and opportunities that da’I has to be optimized, especially with regard to efforts to maintain the beauty and harmony of the universe. The duties of da’i are not limited to delivering matters concerning worship of mahdhoh alone, but da’I also must convey about the obligation to maintain and care for the universe and maintain its balance. Da’I must also be a pioneer of the maintenance of the universe, at least da’I should pioneer in caring and maintaining the environment of the mosque, because the mosque is the house of the Muslim ummah, both for the implementation of Fardhu Prayer, as well as a means of musyawarah and gathering of the Muslims.